A continuous amphiphilic microfiber synergistic oil-water separation membrane
By designing the interfinger-type amphoteric microfiber structure and microfiber transition layer, continuous and efficient separation of the three-phase light oil/water/heavy oil system and a mixture with similar oil-water density without relying on density is achieved, and the separation discontinuity in the prior art is solved and issues that require manual operation.
Patent Information
- Application Number
- CN202410608974.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-16
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-05-16
AI Technical Summary
The existing oil-water separation membrane cannot efficiently separate light oil/water/heavy oil three-phase system or mixture systems with similar oil-water density at the same time, and the separation process is discontinuous, so manual operation is required to change the experimental conditions.
The oil-water separation membrane preparation method with synergistic effect of amphoteric microfibers is used to achieve continuous and efficient separation independent of density-dependent influence through the interdigital structure of polyformaldehyde and geminoxime-formalized polyacrylonitrile microfibers.
Continuous and efficient separation of light oil/water/heavy oil three-phase system and mixtures with similar oil and water density is achieved, with high separation efficiency and no manual operation is required to change the experimental conditions.
Smart Images

Figure CN118416712B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of new material processing and preparation, and relates to a method for preparing a microfiber oil-water separation membrane, and in particular to a method for preparing a continuous amphiphilic microfiber synergistic oil-water separation membrane. Background Art
[0002] In recent years, a series of oil spills at sea have attracted widespread attention from scholars around the world. Therefore, many scholars and experts have focused on the field of oil-water separation in order to invent and prepare efficient, energy-saving and environmentally friendly oil-water separation materials. So far, researchers have made many efforts to prepare a large number of oil-water separation materials. Among them, membrane materials are particularly prominent among many oil-water separation materials due to their advantages such as high separation efficiency, large flux, energy saving and environmental protection, and are also one of the most promising oil-water separation materials. Chen et al. prepared a superhydrophilic-underwater superoleophobic membrane by coating silica nanospheres on glass fibers. The membrane can efficiently separate water-in-oil emulsions, such as light oil / water mixtures such as toluene, n-hexane, and isooctane. Choi et al. successfully designed and prepared an inside-outside fluorinated polyurethane coated fabric material, using polyurethane reaction to modify the internal sites and external surface of the fabric, so that it has excellent hydrophobicity and water-repellency, and can separate water / heavy oil mixtures such as nitromethane, trichloroethylene, chloroform, and chlorobenzene.
[0003] However, there is a problem with the above-mentioned oil-water separation materials, that is, they can only separate a single system of light oil / water or water / heavy oil, but cannot simultaneously separate a three-phase system of light oil / water / heavy oil or a mixture system of oil and water with similar density in a complex environment. Specifically, the oleophilic hydrophobic membrane can separate the water / heavy oil system because the density of the oil phase is greater than that of water, and it contacts the membrane and is adsorbed and separated before water, while the water phase is blocked above the membrane, thereby achieving water / heavy oil separation. Vice versa, the hydrophilic oleophobic membrane can only separate the light oil / water system. In response to this, Liu et al. made improvements and prepared a superhydrophilic / superhydrophobic oil-water separation membrane with opposite wettability on both sides, integrating the oleophilic hydrophobic material and the hydrophilic oleophobic material on the front and back sides of a membrane, realizing the separation of the light oil / water system and the water / heavy oil system using a single membrane. However, the amphiphilic separation membrane still relies on the density effect brought by gravity to cause oil-water stratification to achieve oil-water separation, and cannot achieve continuous separation, that is, the upper liquid phase will accumulate in large quantities as the mixture is continuously added, and cannot be separated continuously. In addition, when the amphiphilic separation membrane separates light oil / water and water / heavy oil systems, the separation membrane needs to be turned over to meet the needs of different wettabilities, that is, manual operation is required to change the experimental conditions, so it has great limitations in the continuous separation of light oil / water / heavy oil three-phase systems or mixed systems with similar oil and water densities.
[0004] Microfibers refer to fibers with diameters ranging from a few microns to hundreds of microns in length. This micron-level size allows them to have a large number of holes formed by the interlacing, overlapping, and supporting of microfibers, which can be used for liquid adsorption and are a very promising oil-water separation material. At present, the methods for preparing microfibers include disassembly, pulping and dispersion, and electrospinning. In previous studies, we have prepared polyoxymethylene microfibers and amidoxime-modified polyacrylonitrile microfibers for oil-water separation by top-down fiber disassembly, and have confirmed that they have fast and efficient oil-water separation performance.
[0005] Polyoxymethylene and amidoxime-treated polyacrylonitrile microfibers have opposite wettabilities—polyoxymethylene microfibers are oleophilic and hydrophobic, while amidoxime-treated polyacrylonitrile microfibers are hydrophilic and oleophobic. Both are prepared by mechanical shearing and disassembly of stretched fibers. Microfibers are plastic and can be filtered into different shapes according to different molds to meet the needs. Therefore, we use the plasticity of these two types of microfibers to filter them together to form a microfiber membrane. The two sides of the membrane are half polyoxymethylene microfibers and half amidoxime-treated polyacrylonitrile microfibers, respectively, so that the two sides of the membrane have opposite wettabilities, and the interface in the middle is the amphiphilic separation interface and microfiber transition layer formed by the two types of microfibers interlacing, overlapping, and supporting each other. Among them, the length of the amphiphilic separation interface and the width of the microfiber transition layer are both controllable. The width of the microfiber transition layer is changed by controlling the vacuum pressure difference when filtering the left microfiber: when filtering the left polyoxymethylene microfiber, the vacuum pressure is controlled to be smaller (larger), so that the polyoxymethylene microfiber has a smaller (larger) density and a larger (smaller) porosity. Therefore, when filtering the amidoxime polyacrylonitrile microfiber on the right, the amidoxime polyacrylonitrile microfiber dispersion can (cannot) penetrate into the polyoxymethylene microfiber side, making the microfiber transition layer wider (narrower). Finally, the vacuum pressure difference of filtering the entire microfiber membrane is increased to make the density and porosity of the two microfibers consistent. The length of the amphoteric separation interface is changed by constructing a forked-finger interface: we adjusted the form of the two microfibers in the above membrane in half, and filtered the two microfibers into a forked-finger type ( Figure 1 ,2), a cross-finger interface was constructed to increase the length of the amphiphilic separation interface, so that the oil-water mixture has a greater chance to contact the separation interface. Finally, under the synergistic effect of the amphiphilic separation interface and the two microfibers, the continuous and efficient separation of oil and water in the light oil / water / heavy oil three-phase system and the mixed system with similar oil and water densities was achieved without relying on the density. The polyoxymethylene and amidoxime-modified polyacrylonitrile microfiber oil-water separation membrane belongs to the amphiphilic oil-water separation material. The physical and chemical stability of the microfiber itself and the large number of pore structures formed by the mutual interlacing, overlapping and supporting of the micropores bring excellent liquid phase wettability and adsorption. The preparation and processing of the two microfibers are simple, low-cost, and recyclable, which makes it have obvious advantages in the large-scale industrial production process. It has certain guiding significance for the development of amphiphilic oil-water separation materials and also provides an effective solution for separating oil-water mixtures of different densities. Summary of the invention
[0006] The purpose of the present invention is to prepare an amphoteric microfiber synergistic oil-water separation membrane which is simple to process, has a significant oil-water separation effect, stable physical and chemical properties, can be repeatedly recycled, has low cost, and can be produced on a large scale and continuously.
[0007] In order to achieve the above object, the present invention provides a preparation scheme of an amphoteric microfiber oil-water separation membrane:
[0008] (1) chopping the polyoxymethylene and polyacrylonitrile stretched fibers with a cutter, and then putting the chopped fibers into water and throwing them into a mechanical crusher for shearing and disassembly to obtain a water dispersion of microfibers of the two fibers;
[0009] (2) The polyacrylonitrile microfiber aqueous dispersion obtained in step (1) is subjected to surface amidoximation modification using hydroxylamine hydrochloride solution to increase surface hydrophilicity, and then filtered, washed, and dried to obtain amidoximated polyacrylonitrile microfibers.
[0010] (3) filtering the polyoxymethylene microfiber aqueous dispersion obtained in step (1) through an interdigitated mold, controlling the vacuum pressure difference during filtration, and obtaining interdigitated polyoxymethylene microfibers on the left side;
[0011] (4) filtering the interdigitated amidoximated polyacrylonitrile microfibers on the right side of the polyoxymethylene microfibers obtained by filtering in step (3), allowing the two microfibers to intersperse, overlap, and support each other at the interface to construct an interdigitated amphoteric separation interface and a microfiber transition layer, and then increasing the vacuum pressure difference to filter the microfiber membrane as a whole;
[0012] (5) A circle of corresponding microfiber dam is filtered on the upper surface of the amphiphilic microfiber separation membrane obtained in step (4) to obtain an oil-water separation membrane with synergistic effect of amphiphilic microfibers.
[0013] Preferably, the length of the chopped fibers in step (1) is about 1-2 cm; in the shearing and disassembly, 10 g of the chopped fibers are mixed with 2 L of water and added to a mechanical pulverizer, the shearing time is 50 min, and the shear rate is 10 5 s -1 .
[0014] Preferably, the concentration of the hydroxylamine hydrochloride solution in step (2) is 4%, the mass of the polyacrylonitrile microfiber is 10 g, the amidoximation modification reaction time is 2 h, and the reaction temperature is 60°C.
[0015] Preferably, the vacuum pressure difference during the filtration of the left microfibers in step (3) is 0.01-0.05 MPa, and the porosity of the left microfibers obtained is 60-85%.
[0016] Preferably, in step (3), the shape of a single interdigital finger is rectangular, the horizontal width is 10-30 mm, preferably 20 mm, the vertical length is 0-5 mm, preferably 5 mm, the number of interdigital fingers of the two microfibers is 0-12, preferably 10, and the two microfibers are distributed alternately. The two interdigital microfibers are the amphoteric separation interface, the length of which is 45-315 mm, preferably 225 mm ( Figure 1 ).
[0017] Preferably, in step (4), the width of the microfiber transition layer is 0.1-0.6 mm, and the vacuum pressure during overall filtration is 0.08 MPa.
[0018] Preferably, the dammed microfibers in step (5) are microfibers corresponding to the membrane surface, and the height of the microfiber dam is 0.5-1.5 mm, preferably 1 mm; the thickness is 2.5 mm ( Figure 1 ); film height is 2-6mm, preferably 4mm, film length is 40-60mm, preferably 50mm, film width is 20-40mm, preferably 30mm ( Figure 2 ).
[0019] Compared with the prior art, the present invention has the following positive and beneficial effects:
[0020] (1) The amphoteric microfiber oil-water separation membrane obtained by the present invention has the characteristics of continuous and efficient separation without relying on oil-water density stratification, and can separate water / heavy oil mixture systems, such as water / chloroform mixtures, and can also separate light oil / water mixture systems, such as cyclohexane / water mixture systems. At the same time, the separated oil and water phases can be transported laterally inside the two microfibers and collected along the designed dredging paths that do not interfere with each other ( Figure 6 ).
[0021] (2) The present invention does not rely on the characteristics of oil-water density separation and can be applied to the separation of light oil / water / heavy oil three-phase mixed systems, such as cyclohexane / water / chloroform three-phase system. The separation can be completed using a single membrane, and there is no need to manually change the experimental conditions during separation. The continuity and high efficiency of oil-water separation can also be maintained. ( Figure 6 ).
[0022] (3) The present invention can separate a mixture system of oil and water with similar density. A mixed oil with a density close to that of water is prepared by using a certain proportion of chloroform and cyclohexane. This mixed oil / water system has no obvious stratification phenomenon due to the similar density. The amphoteric microfiber oil-water separation membrane can continuously and efficiently separate this mixed oil / water system without changing the experimental conditions, and the separated oil and water phases are also collected along their respective dredging paths ( Figure 7 ).
[0023] (4) The interdigitated separation interface of the present invention has amphoteric characteristics. The polyoxymethylene microfiber side at the interface is hydrophobic and oleophilic, while the amidoximized polyacrylonitrile microfiber side is oleophobic and hydrophilic. The two microfibers work synergistically to separate the oil phase and the water phase. Therefore, after the oil-water mixture contacts the interface, it can be adsorbed, transported and separated by the microfibers to which it is affinity. At the same time, the two microfibers with opposite wettability are compounded only by filtration, utilizing the mutual interpenetration, overlap and support characteristics between the microfibers, and the two still maintain their own special wettability ( Figure 4 ).
[0024] (5) The present invention utilizes the designability of the amphiphilic separation interface brought about by the special plasticity of microfibers. Since the oil-water mixture can only be adsorbed and separated by the microfibers to which they are affinity after contacting the amphiphilic separation interface, in order to increase the chance of the oil-water mixture contacting the separation interface, the amphiphilic separation interface is designed into an interdigitated shape by utilizing the plasticity of microfibers, thereby increasing the length of the separation interface.
[0025] (6) The present invention utilizes the designability of the microfiber transition layer brought about by the special plasticity of the microfibers. By controlling the vacuum pressure difference when filtering the microfibers on one side, the density and porosity of the microfibers on this side are different. Therefore, when filtering the microfibers on the other side, the depth of penetration of the dispersion into the already filtered microfiber side is different, thereby changing the width of the microfiber transition layer. For example, the vacuum pressure difference when filtering the polyoxymethylene microfibers on the left side is large, making the polyoxymethylene microfibers denser and having a smaller porosity. Therefore, when filtering the amidoximized polyacrylonitrile microfibers on the right side, the dispersion cannot penetrate too deeply into the polyoxymethylene microfiber side, and the microfiber transition layer is narrower; and vice versa. Finally, the vacuum pressure difference is increased, and the entire microfiber membrane is filtered as a whole to make the density and porosity of the two microfibers consistent. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the preparation process of the amphoteric microfiber separation membrane and its top view and dimensions.
[0027] Figure 2 This is a 3D schematic diagram, size and actual picture of the amphoteric microfiber separation membrane.
[0028] Figure 3 SEM images of polyoxymethylene and polyacrylonitrile microfibers, and SEM and EDS images of the amphoteric separation interface.
[0029] Figure 4 It is the wettability of the amphiphilic microfiber separation membrane to oil and water on both sides and at the amphiphilic separation interface in the liquid phase.
[0030] Figure 5 The wettability of the amphoteric microfiber separation membrane on both sides and at the separation interface to oil (red) and water (blue) in air.
[0031] Figure 6The results show that the amphoteric microfiber separation membrane can be used to separate the cyclohexane / water / chloroform three-phase system.
[0032] Figure 7 It is an amphoteric microfiber separation membrane for the separation of mixed oil / water systems (with a density close to that of water).
[0033] Figure 8 Top view and 3D schematic diagrams of control examples and examples 1-16 (light red represents polyoxymethylene microfibers PMF, light blue represents amidoximized polyacrylonitrile microfibers AOPNF, and dark red and dark blue represent the ring microfiber dams of the corresponding microfibers).
[0034] Fig. 9 Schematic diagram of the width of the microfiber transition layer at the amphoteric separation interface of Examples 3 and 17-20.
[0035] The polyoxymethylene stretched fiber and the polyacrylonitrile fiber are sheared and disassembled in a mechanical pulverizer to obtain polyoxymethylene microfibers and polyacrylonitrile microfibers. Then, the polyacrylonitrile microfibers are subjected to amidoximation hydrophilic modification with hydroxylamine hydrochloride to obtain amidoximated polyacrylonitrile microfibers, wherein the microfiber size is: the diameter range of the polyoxymethylene microfibers is 5-35 μm, and the length range is 50-130 μm; the diameter range of the amidoximated polyacrylonitrile microfibers is 2-12 μm, and the length range is 10-150 μm. The above preparation process and size of polyoxymethylene microfibers and amidoximated polyacrylonitrile microfibers are applied to all the following examples.
[0036] Comparison example
[0037] The polyoxymethylene microfibers were filtered on the left side (vacuum pressure difference 0.03MPa), and then the amidoximized polyacrylonitrile microfibers were filtered next to the polyoxymethylene microfibers on the right side. The two microfibers interlaced, overlapped, and supported each other to form the amphoteric separation interface, which was linear, and the width of the microfiber transition layer was 0.41mm. Under this preparation size, both microfibers were rectangular and 50mm×15mm×4mm in size, and the separation interface length was 45mm. Then, the corresponding 1mm high and 2.5mm thick ring microfiber dam was filtered on the upper surface, and finally a linear amphoteric microfiber oil-water separation membrane was obtained, with an overall size of 50mm×30mm×(4+1)mm( Figure 8 ). At the end of oil-water separation, part of the oil phase and water phase have no residual liquid phase to guide them to contact the separation interface and accumulate on the single microfiber surface on both sides - the water phase accumulates on the surface of polyoxymethylene microfiber, and the oil phase accumulates on the surface of amidoximated polyacrylonitrile microfiber. Therefore, due to the reason that part of the liquid phase cannot be separated, the oil-water separation efficiency is low, which is 93.9% for oil separation efficiency and 94.6% for water separation efficiency. The following examples are based on the size of the control example to design the finger size, membrane size and finger shape transformation.
[0038] Example 1
[0039] The polyoxymethylene microfibers were filtered on the left side (vacuum pressure difference 0.03MPa), and then the amidoximized polyacrylonitrile microfibers were filtered on the right side next to the polyoxymethylene microfibers. The two microfibers interlaced, overlapped, and supported each other to form an amphoteric separation interface, which was in a finger-shaped shape, and the width of the microfiber transition layer was 0.41mm. Under this preparation size, the finger width D = 10mm, the number of fingers N = 4, and the separation interface length was 75mm. Then, the corresponding 1mm high and 2.5mm thick ring microfiber dam was filtered on the upper surface, and finally a finger-shaped amphoteric microfiber oil-water separation membrane was obtained, with an overall size of 50mm×30mm×(4+1)mm( Figure 8 ). At the end of oil-water separation, part of the oil phase and water phase have no residual liquid phase to guide them to contact the separation interface and accumulate on the single microfiber surface on both sides - the water phase accumulates on the surface of polyoxymethylene microfiber, and the oil phase accumulates on the surface of amidoximized polyacrylonitrile microfiber. Therefore, due to the reason that part of the liquid phase cannot be separated, the oil-water separation efficiency is low, which is 93.5% for oil separation efficiency and 93.8% for water separation efficiency respectively.
[0040] Example 2
[0041] The polyoxymethylene microfibers were filtered on the left side (vacuum pressure difference 0.03MPa), and then the amidoximized polyacrylonitrile microfibers were filtered on the right side next to the polyoxymethylene microfibers. The two microfibers interlaced, overlapped, and supported each other to form an amphoteric separation interface, which was a forked finger type, and the width of the microfiber transition layer was 0.41mm. Under this preparation size, the forked finger width D = 10mm, the number of forked fingers N = 10, and the length of the separation interface was 135mm. Then, the corresponding 1mm high and 2.5mm thick ring microfiber dam was filtered on the upper surface, and finally a forked finger type amphoteric microfiber oil-water separation membrane was obtained, with an overall size of 50mm×30mm×(4+1)mm( Figure 8 ). At the end of oil-water separation, part of the oil phase and water phase have no residual liquid phase to guide them to contact the separation interface and accumulate on the single microfiber surface on both sides - the water phase accumulates on the surface of polyoxymethylene microfiber, and the oil phase accumulates on the surface of amidoximized polyacrylonitrile microfiber. Therefore, due to the reason that part of the liquid phase cannot be separated, the oil-water separation efficiency is low, which is 93.1% for oil separation efficiency and 95.6% for water separation efficiency.
[0042] Example 3
[0043] The polyoxymethylene microfibers were filtered on the left side (vacuum pressure difference 0.03MPa), and the amidoximated polyacrylonitrile microfibers were filtered on the right side next to the polyoxymethylene microfibers. The two microfibers interlaced, overlapped, and supported each other to form an amphoteric separation interface, which was interdigitated. The width of the microfiber transition layer was 0.41mm ( Fig. 9). Under this preparation size, the width of the forked finger D = 20 mm, the number of forked fingers N = 10, and the length of the separation interface is 225 mm. Then, the corresponding 1 mm high and 2.5 mm thick ring microfiber dam is filtered on the upper surface, and finally the forked finger type amphoteric microfiber oil-water separation membrane is obtained, with an overall size of 50 mm × 30 mm × (4 + 1) mm ( Figure 8 ). At the end of oil-water separation, there is basically no residual liquid phase accumulated on the single microfiber surface on both sides of the separation interface. Therefore, due to the lack of partial liquid phase accumulation, the oil-water separation efficiency is relatively high, with an oil separation efficiency of 98.7% and a water separation efficiency of 96.7%, respectively. This example is used as a stable separation membrane for experiments because the interdigital size is relatively stable and the membrane size is relatively suitable. The following examples are all obtained by partial design and adjustment based on Example 3.
[0044] Example 4
[0045] The polyformaldehyde microfibers were filtered on the left side (vacuum pressure difference 0.03MPa), and then the amidoximized polyacrylonitrile microfibers were filtered on the right side next to the polyformaldehyde microfibers. The two microfibers interlaced, overlapped, and supported each other to form an amphoteric separation interface, which was finger-shaped, and the width of the microfiber transition layer was 0.41mm. Under this preparation size, due to the limitation of the ring microfiber dam, the effective finger width D in the dam was 25mm, the number of fingers N was 10, and the length of the separation interface was 225mm. Then, the corresponding 1mm high and 2.5mm thick ring microfiber dam was filtered on the upper surface, and finally a finger-shaped amphoteric microfiber oil-water separation membrane was obtained, with an overall size of 50mm×30mm×(4+1)mm( Figure 8 ). At the end of oil-water separation, there is basically no residual liquid phase accumulated on the single microfiber surface on both sides of the separation interface. Therefore, due to the lack of partial liquid phase accumulation, the oil-water separation efficiency is relatively high, which is 98.2% for oil separation and 97.7% for water separation.
[0046] Example 5
[0047] The polyformaldehyde microfibers are filtered on the left side (vacuum pressure difference 0.03MPa), and then the amidoximized polyacrylonitrile microfibers are filtered on the right side next to the polyformaldehyde microfibers. The two microfibers are interlaced, overlapped, and supported with each other to form the amphoteric separation interface, which is finger-shaped, and the width of the microfiber transition layer is 0.41mm. Theoretically, under this preparation size, the finger width D = 20mm, the number of fingers N→∞, and the separation interface length→∞. Then, the corresponding 1mm high and 2.5mm thick ring microfiber dam is filtered on the upper surface, and theoretically, a finger-shaped amphoteric microfiber oil-water separation membrane can be obtained, with an overall size of 50mm×30mm×(4+1)mm( Figure 8). Theoretically, since the separation interface is long enough and there is no accumulation of residual liquid phase on both sides of the interface, it is reasonable to infer that the microfiber separation membrane in this example has high oil-water separation efficiency. However, this is limited to the microfiber separation membrane with infinite separation interface in theory. It has not been prepared in actual experiments. This example is only for theoretical analysis to facilitate understanding.
[0048] Example 6
[0049] The polyformaldehyde microfibers are filtered on the left side (vacuum pressure difference 0.03MPa), and then the amidoximized polyacrylonitrile microfibers are filtered on the right side next to the polyformaldehyde microfibers. The two microfibers are interlaced, overlapped, and supported with each other to form an amphoteric separation interface, which is a forked finger type, and the width of the microfiber transition layer is 0.41mm. Under this preparation size, the forked finger width D = 20mm, the number of forked fingers N = 12, and the length of the separation interface is 275mm. Then, the corresponding 1mm high and 2.5mm thick ring microfiber dam is filtered on the upper surface, and finally a forked finger type amphoteric microfiber oil-water separation membrane is obtained, with an overall size of 60mm×30mm×(4+1)mm. This size is longer than the membrane length in Example 3, so the length of the separation interface is increased, and the area of the separation area surrounded by the ring microfiber dam is also increased, so the volume of the oil-water mixture that can be separated at the same time is also increased ( Figure 8 ). At the end of oil-water separation, there is basically no residual liquid phase accumulated on the single microfiber surface on both sides of the separation interface. Therefore, due to the lack of partial liquid phase accumulation, the oil-water separation efficiency is relatively high, which is 98.1% for oil separation and 98.9% for water separation.
[0050] Example 7
[0051] The polyformaldehyde microfibers are filtered on the left side (vacuum pressure difference 0.03MPa), and then the amidoximized polyacrylonitrile microfibers are filtered on the right side next to the polyformaldehyde microfibers. The two microfibers are interlaced, overlapped, and supported with each other to form an amphoteric separation interface, which is a forked finger type, and the width of the microfiber transition layer is 0.41mm. Under this preparation size, the forked finger width D = 20mm, the number of forked fingers N = 8, and the length of the separation interface is 175mm. Then, the corresponding 1mm high and 2.5mm thick ring microfiber dam is filtered on the upper surface, and finally a forked finger type amphoteric microfiber oil-water separation membrane is obtained, with an overall size of 40mm×30mm×(4+1)mm. This size is smaller than the membrane length of Example 3, so the length of the separation interface is reduced, and the area of the separation area surrounded by the ring microfiber dam is also reduced, so the volume of the oil-water mixture that can be separated at the same time is also reduced ( Figure 8 ). At the end of oil-water separation, there is basically no residual liquid phase accumulated on the single microfiber surface on both sides of the separation interface. Therefore, due to the lack of partial liquid phase accumulation, the oil-water separation efficiency is relatively high, with an oil separation efficiency of 97.5% and a water separation efficiency of 98%, respectively.
[0052] Example 8
[0053] The polyformaldehyde microfibers are filtered on the left side (vacuum pressure difference 0.03MPa), and then the amidoximized polyacrylonitrile microfibers are filtered on the right side next to the polyformaldehyde microfibers. The two microfibers are interlaced, overlapped, and supported with each other to form an amphoteric separation interface, which is a forked finger type, and the width of the microfiber transition layer is 0.41mm. Under this preparation size, the forked finger width D = 10mm, the number of forked fingers N = 10, and the length of the separation interface is 135mm. Then, the corresponding 1mm high and 2.5mm thick ring microfiber dam is filtered on the upper surface, and finally a forked finger type amphoteric microfiber oil-water separation membrane is obtained, with an overall size of 50mm×20mm×(4+1)mm. This size is smaller than the membrane width of Example 3, so the length of the separation interface is reduced, and the area of the separation area surrounded by the ring microfiber dam is also reduced, so the volume of the oil-water mixture that can be separated at the same time is also reduced ( Figure 8 ). At the end of oil-water separation, there is basically no residual liquid phase accumulated on the single microfiber surface on both sides of the separation interface. Therefore, due to the lack of partial liquid phase accumulation, the oil-water separation efficiency is relatively high, which is 97.4% for oil separation efficiency and 97.9% for water separation efficiency.
[0054] Example 9
[0055] The polyformaldehyde microfibers are filtered on the left side (vacuum pressure difference 0.03MPa), and then the amidoximized polyacrylonitrile microfibers are filtered on the right side next to the polyformaldehyde microfibers. The two microfibers are interlaced, overlapped, and supported with each other to form an amphoteric separation interface, which is a forked finger type, and the width of the microfiber transition layer is 0.41mm. Under this preparation size, the forked finger width D = 30mm, the number of forked fingers N = 10, and the length of the separation interface is 315mm. Then, the corresponding 1mm high and 2.5mm thick ring microfiber dam is filtered on the upper surface, and finally a forked finger type amphoteric microfiber oil-water separation membrane is obtained, with an overall size of 50mm×40mm×(4+1)mm. This size is larger than the membrane width of Example 3, so the length of the separation interface is increased, and the area of the separation area surrounded by the ring microfiber dam is also increased, so the volume of the oil-water mixture that can be separated at the same time is also increased ( Figure 8 ). At the end of oil-water separation, there is basically no residual liquid phase accumulated on the single microfiber surface on both sides of the separation interface. Therefore, due to the lack of partial liquid phase accumulation, the oil-water separation efficiency is relatively high, which is 99.2% for oil separation and 99.1% for water separation.
[0056] Example 10
[0057] The polyformaldehyde microfibers are filtered on the left side (vacuum pressure difference 0.03MPa), and then the amidoximized polyacrylonitrile microfibers are filtered on the right side next to the polyformaldehyde microfibers. The two microfibers are interlaced, overlapped, and supported with each other to form an amphoteric separation interface, which is a forked finger type, and the width of the microfiber transition layer is 0.41mm. Under this preparation size, the forked finger width D = 20mm, the number of forked fingers N = 10, and the length of the separation interface is 225mm. Then, the corresponding 1mm high and 2.5mm thick ring microfiber dam is filtered on the upper surface, and finally a forked finger type amphoteric microfiber oil-water separation membrane is obtained, with an overall size of 50mm×30mm×(3+1)mm. This size is smaller than the membrane height in Example 3, but does not affect the length of the separation interface. It only reduces the time for dredging after the liquid phase is adsorbed, so it has an indirect effect on the separation time ( Figure 8 ). At the end of oil-water separation, there is basically no residual liquid phase accumulated on the single microfiber surface on both sides of the separation interface. Therefore, due to the lack of partial liquid phase accumulation, the oil-water separation efficiency is relatively high, which is 98.7% for oil separation and 97.9% for water separation.
[0058] Example 11
[0059] The polyformaldehyde microfibers are filtered on the left side (vacuum pressure difference 0.03MPa), and then the amidoximized polyacrylonitrile microfibers are filtered on the right side next to the polyformaldehyde microfibers. The two microfibers are interlaced, overlapped, and supported with each other to form an amphoteric separation interface, which is a forked finger type, and the width of the microfiber transition layer is 0.41mm. Under this preparation size, the forked finger width D = 20mm, the number of forked fingers N = 10, and the length of the separation interface is 225mm. Then, the corresponding 1mm high and 2.5mm thick ring microfiber dam is filtered on the upper surface, and finally a forked finger type amphoteric microfiber oil-water separation membrane is obtained, with an overall size of 50mm×30mm×(5+1)mm. This size increases the membrane height compared to Example 3, but does not affect the length of the separation interface. It only increases the time for dredging after the liquid phase is adsorbed, so it has an indirect effect on the separation time ( Figure 8 ). At the end of oil-water separation, there is basically no residual liquid phase accumulated on the single microfiber surface on both sides of the separation interface. Therefore, due to the lack of partial liquid phase accumulation, the oil-water separation efficiency is relatively high, which is 98.6% for oil separation and 98.9% for water separation.
[0060] Example 12
[0061] The polyformaldehyde microfibers are filtered on the left side (vacuum pressure difference 0.03MPa), and then the amidoximized polyacrylonitrile microfibers are filtered on the right side next to the polyformaldehyde microfibers. The two microfibers are interlaced, overlapped, and supported with each other to form an amphoteric separation interface, which is a forked finger type, and the width of the microfiber transition layer is 0.41mm. Under this preparation size, the forked finger width D = 20mm, the number of forked fingers N = 10, and the length of the separation interface is 225mm. Then, the corresponding 1.5mm high and 2.5mm thick ring microfiber dam is filtered on the upper surface, and finally a forked finger type amphoteric microfiber oil-water separation membrane is obtained, with an overall size of 50mm×30mm×(4+1.5)mm. This size is higher than the height of the ring microfiber dam in Example 3, but it does not affect the length of the separation interface. However, the increase in the space above the membrane means that the volume of the oil-water mixture separated at the same time is increased ( Figure 8 ). At the end of oil-water separation, there is basically no residual liquid phase accumulated on the single microfiber surface on both sides of the separation interface. Therefore, due to the lack of partial liquid phase accumulation, the oil-water separation efficiency is relatively high, which is 98.2% for oil separation and 97.8% for water separation.
[0062] Example 13
[0063] The polyformaldehyde microfibers are filtered on the left side (vacuum pressure difference 0.03MPa), and then the amidoximized polyacrylonitrile microfibers are filtered on the right side next to the polyformaldehyde microfibers. The two microfibers are interlaced, overlapped, and supported with each other to form an amphoteric separation interface, which is a forked finger type, and the width of the microfiber transition layer is 0.41mm. Under this preparation size, the forked finger width D = 20mm, the number of forked fingers N = 10, and the length of the separation interface is 225mm. Then, the corresponding 0.5mm high and 2.5mm thick ring microfiber dam is filtered on the upper surface, and finally a forked finger type amphoteric microfiber oil-water separation membrane is obtained, with an overall size of 50mm×30mm×(4+0.5)mm. This size is smaller than the height of the ring microfiber dam in Example 3, but it does not affect the length of the separation interface. However, the reduction in space above the membrane means that the volume of the oil-water mixture separated at the same time is increased ( Figure 8 ). At the end of oil-water separation, there is basically no residual liquid phase accumulated on the single microfiber surface on both sides of the separation interface. Therefore, due to the lack of partial liquid phase accumulation, the oil-water separation efficiency is relatively high, which is 98.2% for oil separation efficiency and 97.9% for water separation efficiency.
[0064] Example 14
[0065] The polyformaldehyde microfibers are filtered on the left side (vacuum pressure difference 0.03MPa), and then the amidoximated polyacrylonitrile microfibers are filtered on the right side next to the polyformaldehyde microfibers. The two microfibers are interlaced, overlapped, and supported with each other to form an amphoteric separation interface, which is in the form of a forked finger shape, and the width of the microfiber transition layer is 0.41mm. Under this preparation size, the forked finger width D = 20mm, the number of forked fingers N = 10, and the length of the separation interface is 225mm. Then, the corresponding 1mm high and 2.5mm thick ring microfiber dam is filtered on the upper surface, and finally a forked finger-type amphoteric microfiber oil-water separation membrane is obtained, with an overall size of 50mm×30mm×(4+1)mm. This size is different from Example 3 in that the forked finger form is slightly higher than the amidoximated polyacrylonitrile microfiber in the membrane. The polyformaldehyde microfiber forked fingers are 4mm high as the membrane, and the amidoximated polyacrylonitrile microfiber height is 2mm( Figure 8 ). At the end of oil-water separation, there is basically no residual liquid phase accumulated on the single microfiber surface on both sides of the separation interface. Therefore, due to the lack of partial liquid phase accumulation, the oil-water separation efficiency is relatively high, which is 95.6% for oil separation and 96.9% for water separation.
[0066] Example 15
[0067] The polyformaldehyde microfibers are filtered on the left side (vacuum pressure difference 0.03MPa), and then the amidoximated polyacrylonitrile microfibers are filtered on the right side next to the polyformaldehyde microfibers. The two microfibers are interlaced, overlapped, and supported with each other to form an amphoteric separation interface, which is in the form of a forked finger shape, and the width of the microfiber transition layer is 0.41mm. Under this preparation size, the forked finger width D = 20mm, the number of forked fingers N = 10, and the length of the separation interface is 225mm. Then, the corresponding 1mm high and 2.5mm thick ring microfiber dam is filtered on the upper surface, and finally a forked finger-type amphoteric microfiber oil-water separation membrane is obtained, with an overall size of 50mm×30mm×(4+1)mm. This size is different from Example 3 in that the forked finger form is slightly higher than the polyformaldehyde microfiber in the membrane. The forked fingers of the amidoximated polyacrylonitrile microfibers are 4mm high as the membrane, and the height of the polyformaldehyde microfibers is 2mm ( Figure 8 ). At the end of oil-water separation, there is basically no residual liquid phase accumulated on the single microfiber surface on both sides of the separation interface. Therefore, due to the lack of partial liquid phase accumulation, the oil-water separation efficiency is relatively high, which is 97.7% for oil separation and 98.2% for water separation.
[0068] Example 16
[0069] The polyformaldehyde microfibers are filtered on the left side (vacuum pressure difference 0.03MPa), and then the amidoximized polyacrylonitrile microfibers are filtered on the right side next to the polyformaldehyde microfibers. The two types of microfibers are interlaced, overlapped, and supported with each other to form an amphoteric separation interface, which is a forked finger type, and the width of the microfiber transition layer is 0.41mm. Under this preparation size, the forked finger width D = 20mm, the number of forked fingers N = 10, and the length of the separation interface is 225mm. Then, the corresponding 1mm high and 2.5mm thick ring microfiber dam is filtered on the upper surface, and finally a forked finger type amphoteric microfiber oil-water separation membrane is obtained, with an overall size of 50mm×30mm×(4+1)mm. This size is different from Example 3 in that the side of the forked finger shape is a right-angled triangle, and the surface of the microfiber membrane is inclined inward along the hypotenuse of the triangle plate from the long side ( Figure 8 ). At the end of oil-water separation, there is basically no residual liquid phase accumulated on the single microfiber surface on both sides of the separation interface. Therefore, due to the lack of partial liquid phase accumulation and the inclination of the membrane surface, the oil-water separation efficiency is relatively high, with an oil separation efficiency of 98.9% and a water separation efficiency of 99.5%.
[0070] Example 17
[0071] The polyoxymethylene microfibers were filtered on the left side (vacuum pressure difference 0.01MPa), and the amidoximated polyacrylonitrile microfibers were filtered on the right side next to the polyoxymethylene microfibers. The two microfibers interlaced, overlapped, and supported each other to form an amphoteric separation interface, which was interdigitated. The width of the microfiber transition layer was 0.58mm ( Fig. 9 ). Under this preparation size, the width of the fork finger D = 20mm, the number of forks N = 10, and the length of the separation interface is 225mm. Then, the corresponding 1mm high and 2.5mm thick ring microfiber dam is filtered on the upper surface, and finally a fork-type amphoteric microfiber oil-water separation membrane is obtained, with an overall size of 50mm×30mm×(4+1)mm. Based on Example 3, this example reduces the vacuum pressure difference when filtering the left microfiber (PMF) to 0.01MPa, so the porosity increases to 84.5%, and the dispersion of the right microfiber (AOPNF) can penetrate into the left microfiber, resulting in an increase in the width of the microfiber transition layer to 0.58mm. At the end of the oil-water separation, there is basically no residual liquid phase accumulated on the single microfiber surface on both sides of the separation interface. Therefore, due to the reason that there is no partial liquid phase accumulation and separation, the oil-water separation efficiency is relatively high, with an oil separation efficiency of 98.9% and a water separation efficiency of 97.8%, respectively.
[0072] Example 18
[0073] The polyoxymethylene microfibers were filtered on the left side (vacuum pressure difference 0.02MPa), and the amidoximated polyacrylonitrile microfibers were filtered on the right side next to the polyoxymethylene microfibers. The two microfibers interlaced, overlapped, and supported each other to form an amphoteric separation interface, which was interdigitated. The width of the microfiber transition layer was 0.5mm ( Fig. 9). Under this preparation size, the width of the fork finger D = 20mm, the number of forks N = 10, and the length of the separation interface is 225mm. Then, the corresponding 1mm high and 2.5mm thick ring microfiber dam is filtered on the upper surface, and finally a fork-type amphoteric microfiber oil-water separation membrane is obtained, with an overall size of 50mm×30mm×(4+1)mm. Based on Example 3, this example reduces the vacuum pressure difference when filtering the left microfiber (PMF) to 0.02MPa, so the porosity increases to 76.4%, and the dispersion of the right microfiber (AOPNF) can penetrate into the left microfiber, resulting in an increase in the width of the microfiber transition layer to 0.5mm. At the end of oil-water separation, there is basically no residual liquid phase accumulated on the single microfiber surface on both sides of the separation interface. Therefore, due to the reason that there is no partial liquid phase accumulation and separation, the oil-water separation efficiency is relatively high, with an oil separation efficiency of 97.5% and a water separation efficiency of 97.3%, respectively.
[0074] Example 19
[0075] The polyoxymethylene microfibers were filtered on the left side (vacuum pressure difference 0.04MPa), and the amidoximated polyacrylonitrile microfibers were filtered on the right side next to the polyoxymethylene microfibers. The two microfibers interlaced, overlapped, and supported each other to form an amphoteric separation interface, which was interdigitated. The width of the microfiber transition layer was 0.24mm ( Fig. 9 ). Under this preparation size, the width of the fork finger D = 20mm, the number of forks N = 10, and the length of the separation interface is 225mm. Then, the corresponding 1mm high and 2.5mm thick ring microfiber dam is filtered on the upper surface, and finally a fork-type amphoteric microfiber oil-water separation membrane is obtained, with an overall size of 50mm×30mm×(4+1)mm. This example adds a vacuum pressure difference of 0.04MPa when filtering the left microfiber (PMF) on the basis of Example 3, so the porosity is reduced to 70.1%, and the dispersion of the right microfiber (AOPNF) can penetrate into the left microfiber, resulting in the width of the microfiber transition layer being reduced to 0.24mm. At the end of oil-water separation, there is basically no residual liquid phase accumulated on the single microfiber surface on both sides of the separation interface. Therefore, due to the reason that there is no partial liquid phase accumulation and separation is impossible, the oil-water separation efficiency is relatively high, with an oil separation efficiency of 96.4% and a water separation efficiency of 98.1%, respectively.
[0076] Example 20
[0077] The polyoxymethylene microfibers were filtered on the left side (vacuum pressure difference 0.05MPa), and the amidoximated polyacrylonitrile microfibers were filtered on the right side next to the polyoxymethylene microfibers. The two microfibers interlaced, overlapped, and supported each other to form an amphoteric separation interface, which was interdigitated. The width of the microfiber transition layer was 0.16mm ( Fig. 9). Under this preparation size, the width of the fork finger D = 20mm, the number of forks N = 10, and the length of the separation interface is 225mm. Then, the corresponding 1mm high and 2.5mm thick ring microfiber dam is filtered on the upper surface, and finally a fork-type amphoteric microfiber oil-water separation membrane is obtained, with an overall size of 50mm×30mm×(4+1)mm. This example adds a vacuum pressure difference of 0.05MPa when filtering the left microfiber (PMF) on the basis of Example 3, so the porosity is reduced to 62.9%, and the dispersion of the right microfiber (AOPNF) can penetrate into the left microfiber, resulting in the width of the microfiber transition layer being reduced to 0.16mm. At the end of the oil-water separation, there is basically no residual liquid phase accumulated on the single microfiber surface on both sides of the separation interface. Therefore, due to the reason that there is no partial liquid phase accumulation and separation is impossible, the oil-water separation efficiency is relatively high, with an oil separation efficiency of 97.6% and a water separation efficiency of 97.1%, respectively.
[0078] Separation interface length calculation formula:
[0079] S=V+H=V+(N-1)×D
[0080] S is the total length of the amphiphilic separation interface, V is the total vertical length of the separation interface, H is the total horizontal width of the separation interface, D is the horizontal width of a single interdigital finger, and N is the number of interdigits in the vertical direction.
[0081] Comparative example: S = V + H = V + (N-1) × D = 45 + (0-1) × 0 = 45 mm
[0082] Example 1: S = V + H = V + (N-1) × D = 45 + (4-1) × 10 = 75 mm
[0083] Example 2: S = V + H = V + (N-1) × D = 45 + (10-1) × 10 = 135 mm
[0084] Example 3: S = V + H = V + (N-1) × D = 45 + (10-1) × 20 = 225 mm
[0085] Example 4: S = V + H = V + (N-1) × D = 0 + (10-1) × 25 = 225 mm
[0086] Example 5: S = V + H = V + (N-1) × D → ∞ (N → ∞)
[0087] Example 6: S = V + H = V + (N-1) × D = 55 + (12-1) × 20 = 275 mm
[0088] Example 7: S = V + H = V + (N-1) × D = 35 + (8-1) × 20 = 175 mm
[0089] Example 8: S = V + H = V + (N-1) × D = 45 + (10-1) × 10 = 135 mm
[0090] Example 9: S = V + H = V + (N-1) × D = 45 + (10-1) × 30 = 315 mm
[0091] Example 10-20: S = V + H = V + (N-1) × D = 45 + (10-1) × 20 = 225 mm
[0092] Oil-water separation efficiency calculation formula:
[0093] Oil-water separation efficiency = (V 分离后 / V 分离前 )×100%
[0094] V 分离后 is the volume of the liquid phase after separation, V 分离前 is the volume before liquid phase separation.
[0095]
Claims
1. A method for preparing an amphoteric microfiber oil-water separation membrane, characterized in that: The preparation steps are as follows: (1) First, the prepared polyoxymethylene microfibers are filtered on the left half side using an interdigitated mold to obtain interdigitated polyoxymethylene microfibers on the left half side; (2) filtering the interdigitated amidoximated polyacrylonitrile microfibers on the right side of the polyoxymethylene microfibers obtained by suction filtration in step (1), constructing an interdigitated amphoteric separation interface and a microfiber transition layer, and obtaining an interdigitated amphoteric microfiber oil-water separation membrane; (3) A circle of corresponding microfiber dam is filtered on the upper surface of the interdigitated amphoteric microfiber oil-water separation membrane obtained in step (2).
2. The method for preparing an amphoteric microfiber oil-water separation membrane according to claim 1, characterized in that: The height of the interdigitated amphoteric microfiber oil-water separation membrane obtained by filtration in step (2) is 4-6 mm, the length of the membrane is 40-60 mm, and the width of the membrane is 20-40 mm.
3. The method for preparing an amphoteric microfiber oil-water separation membrane according to claim 1, characterized in that: The top view of a single interdigital structure constructed of the two types of microfibers is rectangular, with a horizontal width of 10-30 mm, a maximum vertical length of 12.5 mm, and a minimum vertical length that is infinitely close to 0. The interdigital fingers are alternately distributed along the long sides of the interdigitated amphoteric microfiber oil-water separation membrane with polyoxymethylene microfibers and amidoxime-treated polyacrylonitrile microfibers, and the total number is 4 to infinity.
4. The method for preparing an amphoteric microfiber oil-water separation membrane according to claim 1, characterized in that: The total length of the interdigitated amphoteric microfiber separation interface constructed in step (2) is 45-315 mm.
5. The method for preparing an amphoteric microfiber oil-water separation membrane according to claim 1, characterized in that: In step (2), the microfiber transition layer is controlled by the vacuum pressure difference during filtration, the vacuum pressure difference range is 0.01-0.05MPa, and the width range of the microfiber transition layer is 0.1-0.6mm.
6. The method for preparing an amphoteric microfiber oil-water separation membrane according to claim 1, characterized in that: The microfibers dammed in step (3) correspond to the membrane microfibers below; the height of the ring microfiber dam is 0.5-1.5 mm and the thickness is 2.5 mm.
7. An amphoteric microfiber oil-water separation membrane, characterized in that: Prepared by the preparation method described in any one of claims 1 to 5.
Citation Information
Patent Citations
Amidoxime polyacrylonitrile fiber and preparation method and application thereof
CN111118884A
Polyformaldehyde microfiber oil-water separation material and preparation method thereof
CN115722209A